Self-propagating high-temperature synthesis technology for preparation of porous permeable materials; Refractories and Industrial Ceramics; Vol. 46, N 6 - Vereshchagin (Vereschagin, Vereshagin) V. I. Vladimir Ivanovich; Evstigneev V. V.; Kolesnikov D. V.; Prolubnikov V. I.; Tubalov N. P. (2005, 2005)
The principles for development of porous permeable materials based on the self-propagating high-temperature synthesis are discussed. A technology based on the use of industrial oxide wastes from the mechanical engineering industry is proposed